A vortex-based method for improved flexible flapping-foil thruster performance. (October 2018) - Priovolos, A.K.; Filippas, E.S.; Belibassakis, K.A.
Abstract: A vortex-based method is presented for the hydroelastic analysis of a hydrofoil in flapping motion, operating as a biomimetic thruster. The system performs combined heaving and pitching motion with appropriate phase difference. As a first approximation, the foil is assumed to be very thin permitting to neglect thickness effects as higher-order contributions to the hydrodynamics. Moreover, the flapping thruster is considered to be flexible, free to deform under inertia and reactive forces caused by its forced motion and hydrodynamic pressure, respectively. The proposed method is validated through a series of comparisons with other models, as well as experimental results, for the case where the foil is clamped at its leading edge, while its trailing edge acts as a free end. It is illustrated that chordwise flexibility can significantly improve the propulsive efficiency. For demonstration purposes, a realistic propulsion problem concerning an autonomous underwater vehicle (AUV) is studied, indicating an efficiency increase almost 10% in comparison with the rigid case. The present method can serve as a useful tool for the preliminary design, as well as for the assessment and dynamic control of such biomimetic systems for marine propulsion and energy recovery.